Power and Responsibility: Shifting Discourses of Gender and HIV/AIDS - Strebel, Anna; Lindegger, Graham (PINS-Psychology in Society, 2026)
HIV/AIDS appeared in the early 1980s as a new and serious health problem. Its apparently incurable and untreatable nature posed a major challenge to biomedical technology. Research into modes of transmission indicated that this was not a "neutral" disease, but one which reflected social divisions of gender, class and ethnicity in vulnerability to HIV. With heterosexual spread of the disease in·developing countries, women’s increased risk of infection was highlighted. As a result, the role of power inequalities in gender relations and the impact of differential access to economic resources were recognised as significant to HIV/AIDS interventions. Thus both social and medical sciences were mobilised and knowledge about the disease rapidly expanded, shifted, accommodated new understandings.